Od dyplomatyki i edytorstwa źródeł ku specjalności archiwalno-edytorskiej : koncepcje kształcenia archiwistów na Uniwersytecie Wrocławskim K. Maleczyńskiego i W. Korty - Harc, Lucyna (Národní archiv, 2021)
Education of archivists at the Wrocław University had its beginning in the academic year 1960/1961 as the result of long-time endeavour of Professor Dr. Karol Maleczyński who took a professional preparation for archivists as a necessity. He himself had worked as an archivist in Lwów since 1925, at first in the Land Archives, then in the State Archives and after habilitation in 1929 he was connected to the Jan Kazimir University in Lwów. His experience from archivalwork and his own contribution to editing sources as in Kodeks Dyplomatyczny Ślaska caused professor Maleczyński for many years to strive for establishment of the Department of Auxiliary Sciences of History and Archival Science (Katedra Nauk Pomocniczych Historii i Archiwistyki) in Wrocław which was establishedas late as in 1960. He created a team of experts who did research in the field of diplomatics, later called a "Wrocław school".